2021
DOI: 10.1038/s41598-021-93540-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping habitat suitability for Asiatic black bear and red panda in Makalu Barun National Park of Nepal from Maxent and GARP models

Abstract: Habitat evaluation is essential for managing wildlife populations and formulating conservation policies. With the rise of innovative powerful statistical techniques in partnership with Remote Sensing, GIS and GPS techniques, spatially explicit species distribution modeling (SDM) has rapidly grown in conservation biology. These models can help us to study habitat suitability at the scale of the species range, and are particularly useful for examining the overlapping habitat between sympatric species. Species pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 66 publications
0
30
0
3
Order By: Relevance
“…In this study, MaxEnt 3.4.1 (https://biodiversityinformatics.amnh.org/open_source/ maxent/, last accessed on 1 July 2021) was used to simulate the potential suitable habitat areas of G. pensilis under the LIG, the LGM, MH, Current and four scenarios in the future (RCP2.6-2050s RCP2.6-2070s, RCP8.5-2050s and RCP8.5-2070s) [17,46]. In order to make the probability of occurrence close to a normal distribution, 75% of the data were selected for model training, the remaining data were used for model testing and other values were the default values [18][19][20][21]. The EMNeval [41,47] package in R (Cran) version 3.6.1 [48] was used to optimize the MaxEnt model and the regularization multiplier (RM) was set to 0.5-4, with intervals of 0.5 each and a total of 8 regulated frequency multipliers.…”
Section: Model Building Optimization and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, MaxEnt 3.4.1 (https://biodiversityinformatics.amnh.org/open_source/ maxent/, last accessed on 1 July 2021) was used to simulate the potential suitable habitat areas of G. pensilis under the LIG, the LGM, MH, Current and four scenarios in the future (RCP2.6-2050s RCP2.6-2070s, RCP8.5-2050s and RCP8.5-2070s) [17,46]. In order to make the probability of occurrence close to a normal distribution, 75% of the data were selected for model training, the remaining data were used for model testing and other values were the default values [18][19][20][21]. The EMNeval [41,47] package in R (Cran) version 3.6.1 [48] was used to optimize the MaxEnt model and the regularization multiplier (RM) was set to 0.5-4, with intervals of 0.5 each and a total of 8 regulated frequency multipliers.…”
Section: Model Building Optimization and Evaluationmentioning
confidence: 99%
“…The maximum entropy (MaxEnt) [16] model is the most commonly used prediction model for the potential distribution area of species; it has a high prediction accuracy and good versatility [17]. This model is widely used to predict the distribution of invasive species [18], endangered animals and plants [19][20][21], natural disasters [22] and pests and diseases [23,24]. It can also be used for Wildfire Risk Assessment and Zoning [25].…”
Section: Introductionmentioning
confidence: 99%
“…A wider landscape study, involving eight countries in the Hindu Kush mountains, employed presence points from multiple sources and explored the effects of 19 bioclimatic variables and 5 topographic or land use variables in a Maxent model; this study mapped the region of suitable habitat but did not provide specific information about what was considered most suitable, except in terms of elevation (1500-3000 m) [125]. Two Maxent models in a national park in Nepal, using the exact same presence data but employing different variables obtained similar range maps, but one used only variables related to topography and land cover [122], whereas the other used primarily bioclimatic variables and concluded that mean temperature was the strongest predictor of Asiatic black bear presence [126]. Given the wide latitudinal range of Asiatic black bears, from the tropics to the subarctic, it would seem doubtful that temperature per se significantly impacts where they occur, although the temperature was likely coarsely related to habitat features on the ground, especially sources of food.…”
Section: Asiatic Black Bearsmentioning
confidence: 99%
“…MaxEnt has been widely used to estimate habitat suitability and thus predict the geographic distribution of a variety of species [29], including both European and North American bison [30,31]. The output of MaxEnt modelling provides an estimated probability of species occurrence based on environmental variables, and we join others in referring to this as synonymous to habitat suitability [29,32,33].…”
Section: Bottom-up Effects On Bisonmentioning
confidence: 99%